CAD/CAM design and 3D printing of a personalised rapid palatal expander for maxillary transverse deficiency - Chunlin Wang; Xiaosong Xiang; Qin Mao; Conghua Liu (Journal of the Pakistan Medical Association, 2023)
Bone-borne rapid maxillary expansion appliances can achieve skeletal expansion while avoiding the undesirable dental side effects caused by a conventional rapid palatal expansion appliance. Typically, these (bone-borne appliances) included prefabricated devices, which can have limitations such as inadequate palatal adaptation leading to anchorage loss. In addition, as bone thickness is not accounted for, prefabricated expanders cannot ensure the primary stability of the mini-implants. These disadvantages can be overcome by customisation. This report aims to describe the digital design and three-dimensional printing workflow for constructing a personalised rapid palatal expander (pMARPE) and present a case depicting its application in a 27-year-old female with 5.0 mm transverse discrepancy between the maxilla and the mandible. The result demonstrated that the pMARPE could be manufactured without the need for conventional impression or laboratory procedures and effectively expanded the palate of an adult patient with maxillary transverse deficiency.